Solidifying dust suppressant based on modified chitosan and experimental study on its dust suppression performance - Yanghao Liu; Wen Nie; Hu Jin; He Ma; Yun Hua; Peng Cai; Wenle Wei (Adsorption Science & Technology)
In view of the fugitive dusts caused by wind disturbance and material handling in coal bunkers, surface plants, and open-air coal stocking yards of coal businesses, the solidifying dust suppressant based on modified chitosan is synthesized and prepared through the chemical modification of –NH 2 with chitosan as a raw material and –NH 2 was replaced by –CH 2 CH(OH)CH 2 N + (CH 3 )CI − through the technique of Fourier transform infrared spectroscopy. According to viscosity experiment results, the viscosity of the modified solidifying dust suppressant increased significantly. The coal particles suppressed by the dust suppressant as observed with a 50,000X scanning electron microscope were coagulated together, which indicated very good cohesion effect. In addition, wind erosion resistance experiment was conducted to analyze the wind erosion rate of coal powders before and after sprayed with the suppressant at different wind speeds, which indicated that the dust suppressant can effectively prevent fugitive dusts at a wind speed of 17 m/s.